Evaluation of preventive screening cytology performed by menopausal women - Bakalczuk, Grzegorz; Wdowiak, Artur; Lewicka, Magdalena; Bąk, Magdalena; Bakalczuk, Szymon; Kanadys, Katarzyna (Menopause Review/Przegląd Menopauzalny, 2012)
Introduction : In Poland, among malignant neoplasms of the genital female organs, the cervical cancer of the uterus ranks the second following the breast cancer as for the frequency of incidence. Cytology is an essential screening test in diagnosis, prophylaxis and early detection of cervical carcinoma. Cytology effectively reduces the risk of cervical carcinoma. Aim of the study : The aim of this study was to evaluate cytology being performed by women. Material and methods : 200 randomly chosen women were examined in this study. The examinations were performed using a questionnaire prepared by authors specifically for this study. Results were then statistically analyzed. Results were statistically significant for p < 0.05. Results : This study shows that 43% of women have cytology performed regularly, while 57% do not. Among 200 (100%) examined women, 65 (32.5%) had cytology tests performed within the last two years, whereas 22 (11%) do not remember when they had cytology performed, and 43 (21.5%) have never this examination performed. Conclusions : Medical staff should take actions aiming to increase women’s consciousness about necessity of visiting their gynecologists. Women aged 46-50 and over 60 years old should be provided with primary education about preventive screening cytology.